Blood Pressure Control and Its Determinants among Patients with Non-Dialysis Chronic Kidney Disease in Myanmar - Ei Su Mon; Aurawamon Sriyuktasuth; Warunee Phligbua (Diponegoro University, 2022)
Background: Controlling blood pressure is critical for patients with non-dialysis chronic kidney disease to prevent the rapid progression to end-stage renal disease and sudden cardiac death. However, only a limited number of these patients achieve the blood pressure target. No previous study has been observed to evaluate the status of blood pressure control and its determinants among Myanmar patients with non-dialysis chronic kidney disease. Purpose: This study aimed to identify the rate of blood pressure control and its determinants among patients with non-dialysis chronic kidney disease in Myanmar. Methods: A total of 150 patients with non-dialysis chronic kidney disease attending the clinics at a tertiary hospital in Myanmar participated in this cross-sectional, correlational predictive study. They were recruited by a convenience sampling method. Data were collected by using Sodium Consumption Behavior Questionnaire, Family-Friends Support Subscale and Doctor-Health Care Team Support Subscale of Chronic Illness Resources Survey, demographic and clinical characteristics data form, and by measuring blood pressure against the target level of less than 130/80 mmHg. Descriptive statistics, Chi-square, Fisher's exact test, and binary logistic regression analysis were performed. Results: Only 44% of the participants had their blood pressure controlled. Overweight (OR=0.170, 95% CI: 0.058-0.495), obese (OR=0.071, 95% CI: 0.017-0.305), and chronic kidney disease stage 5 (OR=0.070, 95% CI: 0.020-0.244)  were the determinants associated with poorly controlled blood pressure. Low sodium consumption behavior (OR=9.065, 95% CI: 3.251-25.277) and high family support (OR=7.799, 95% CI: 2.738-22.215) were the determinants associated with well-controlled blood pressure. Conclusion: The blood pressure control rate in Myanmar patients with non-dialysis chronic kidney disease was suboptimal. Determinant findings serve as an input to endorse family-based lifestyle modification interventions such as weight control and low sodium dietary for optimizing blood pressure control. Further investigation of other determinants and of lifestyle intervention programs is warranted.